Mountains of millipedes. The family Odontopygidae in the Eastern Arc Mountains of Tanzania (Diplopoda, Spirostreptida) - Enghoff, Henrik (European Journal of Taxonomy, 2022)
The fauna of the millipede family Odontopygidae in the Eastern Arc Mountains of Tanzania is reviewed. Species from the North Pare, South Pare, West Usambara, East Usambara, Nguru, Rubeho, Uluguru and Rungwe Mts are treated. The odontopygids of the Udzungwa Mts have been subject of a series of previous papers and are only treated marginally. Six new genera and 25 new species are described: Antipustia gen. nov., Aptyctosmilax gen. nov., Multipronopea gen. nov., Notogallanus gen. nov., Praludivera gen. nov., Uncodrama gen. nov., Antipustia hoteldolichoiuli gen. et sp. nov., Aptyctosmilax helenae gen. et sp. nov., Calyptomastix ingemanni sp. nov., Calyptomastix vuasu sp. nov., Calyptomastix xystopygoides sp. nov., Calyptomastix zoltani sp. nov., Chaleponcus jolantae sp. nov., Chaleponcus nesrineae sp. nov., Chaleponcus schioetzae sp. nov., Chaleponcus sergeii sp. nov., Chaleponcus soerensenae sp. nov., Geotypodon cristinae sp. nov., Lamelloramus frederiksenae sp. nov., Multipronopea agneteae gen. et sp. nov., Notogallanus mastacembalus gen. et sp. nov., Praludivera paralellamella gen. et sp. nov., Raduliverpa donatellae sp. nov., Spinotarsus axeli sp. nov., Syndesmogenus estelleae sp. nov., Uncodrama coronata gen. et sp. nov., Xystopyge bentemarieae sp. nov., Xystopyge doggartae sp. nov., Xystopyge hippocampus sp. nov., Xystopyge minnae sp. nov., and Xystopyge voluntariorum sp. nov. The discussion focuses on diversity and distribution patterns, the justification for monotypic (monospecific) genera, and the following morphological character types: the ozopore series, the limbus, the number of setae on the anal valves, the first pair of male legs, the gonopod sternum, and the sternum of the rudimentary 9th leg-pair.